SMEs Innovativeness and Institutional Support System: The Local Experiences in Qualitative Perspective - Anna Lewandowska; Mateusz Stopa (Institute of Economic Research (IER), 2017)
Innovations are considered to be one of the most progressive determinants of socio-economic growth, also in the regional and local perspective (compare Petrariu, et al., 2013; Priede & Pereira 2013; Sternberg & Arndt, 2001). The high level of innovation has a positive impact on productivity at the firm level (business performance, see, e.g. Bhaskaran, 2006) and consequently also on the economic results at regional or national level (economic performance, see, e.g. DiPietro & Anoruo, 2006). The aim of this paper is to contribute to a greater understanding of the research on institutional support system for SMEs innovativeness in the Podkarpackie region. In analyzing this case, we raise the following two questions: (1) what are the types of innovation strategies of SMEs in Podkarpackie?; (2) what are the factors affecting innovation and potential barriers to further use of institutional support system aimed at the implementation of innovation in enterprises. The study was qualitative interviews (in-depth interviews - IDI) with key individuals in SME's, R&D units, business environment institutions, regional and local authorities. Based on the opinion of entrepreneurs and others, evaluated programs and projects dedicated to innovation and identified barriers encountered by entrepreneurs limiting the implementation of innovation. Made in this way to assess the effectiveness of institutional support system. The results of our research show that institutional support system mitigate negative consequences of peripheral localization of the enterprises, where specific innovation strategy has no influence on SMEs assessment of innovation effectiveness. The innovation is too costly and SMEs are too weak in peripheral region, therefore there is great need for reasonable and flexible institutional support system. However, peripheral situation influences this institutional system itself, strengthening the mechanisms of self-cenzorship.
Keywords: L25; O12; O33; 330; innovation; innovation strategies; SMEs; institutional support system